Exploring acceptability, opportunities, and challenges of community-based home pregnancy testing for early antenatal care initiation in rural Kenya - Lilian Otiso; Yussif Alhassan; Tom Odhong; Boniface Onyango; Nelly Muturi; Charlotte Hemingway; Lois Murray; Emily Ogwang; Linet Okoth; Mandela Oguche; Vicki Doyle; Nadia Fomuso; et al. (BMC, 2024)
Abstract Background Many women in low- and middle-income countries, including Kenya, access antenatal care (ANC) late in pregnancy. Home pregnancy testing can enable women to detect pregnancy early, but it is not widely available. Our study explored the acceptability and potential of home pregnancy testing delivered by community health volunteers (CHV) on antenatal care initiation in rural Kenya. Methods This study was part of a public health intervention to improve uptake and quality of ANC. Between November and December 2020, we conducted 37 in-depth interviews involving women who tested positive or negative for a urine pregnancy test provided by CHVs; CHVs and their supervisors involved in the delivery of the pregnancy tests; facility healthcare workers; and key informants. Using Sekhon et al.'s framework of acceptability, the interviews explored participants' perceptions and experiences of home pregnancy testing, including acceptability, challenges, and perceived effects on early ANC uptake. Data were analysed thematically in NVivo12 software. Results Home pregnancy testing was well-received by women who trusted test results and appreciated the convenience and autonomy it offered. Adolescents cherished the privacy, preferring home testing to facility testing which could be a stigmatising experience. Testing enabled earlier pregnancy recognition and linkage to ANC as well as reproductive decision-making for those with undesired pregnancies. Community delivery of the test enhanced the reputation and visibility of the CHVs as credible primary care providers. CHVs in turn were motivated and confident to deliver home pregnancy testing and did not find it as an unnecessary burden; instead, they perceived it as a complement to their work in providing ANC in the community. Challenges identified included test shortages, confidentiality and safeguarding risks, and difficulties accessing facility-based care post-referral. Newly identified pregnant adolescents hesitated to seek ANC due to stigma, fear of reprimand, unwanted parental notification, and perceived pressure from healthcare workers to keep the pregnancy. Conclusion Home pregnancy testing by CHVs can improve early ANC initiation in resource-poor settings. Mitigating privacy, confidentiality, and safeguarding concerns is imperative. Additional support for women transitioning from pregnancy identification to ANC is essential to ensure appropriate care. Future research should focus on integrating home pregnancy testing into routine community health services.